Debt Limits in Fund-Supported Programs : Proposed New Guidelines. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This supplement summarizes the reforms proposed in IMF (2009a, b)1 to the existing framework governing external debt limits in Fund-supported programs, and presents the proposed decision that is needed to implement these reforms. The supplement is organized as follows: Section II provides a brief commentary on the proposed decision, emphasizing key aspects of the proposed reforms set out in IMF (2009a, b) 1. Section III contains the proposed decision approving the new guidelines on external debt in Fund arrangements. The proposed new guidelines are included in the Attachment to the decision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Arrangement; Methodology; PP; PRGF